Financial accounting : tools for business decision making - Weygandt, Jerry J.; Kieso, Donald E.; Kimmel, Paul D. (New York ; Chichester : John Wiley & Sons, 2000)
This book contains an introduction to Financial Statements; Accounting information systems; Merchandising operations;...
Keywords: Accounting; Financial accounting; Accounting